Evaluating the use of heparin for synchronization of in vitro culture of Plasmodium falciparum. Issue 5 (October 2016) - Kobayashi, Kyousuke; Kato, Kentaro
Abstract: The malaria parasite Plasmodium falciparum infects human erythrocytes and reproduces asexually through an intraerythrocytic developmental cycle. In vitro culture of P. falciparum allows investigation of the parasite's blood-stage development, which spans approximately 48 h from the time of invasion to the lysis of mature schizonts to release merozoites. To focus on a specific step in the developmental cycle, synchronization techniques are utilized.d -Sorbitol treatment and the Percoll-sorbitol method have been used; however, these techniques have limitations in terms of the degree of synchronization achieved, the amount of synchronized parasite acquired, convenience, reproducibility, and cost. Here, we evaluated an existing synchronization method involving heparin. Heparin reversibly inhibits erythrocyte invasion by P. falciparum merozoites. We confirm that parasite cultures can be inexpensively, reproducibly, and tightly synchronized by combining a sorbitol step to limit cultures to the ring stages and by adding and removing heparin to manipulate the window during which merozoites can invade erythrocytes. Highlights: This method enables synchronization of P. falciparum in vitro culture to be simple, reproducible, and inexpensive. This method is based on the nature of heparin that reversibly inhibits erythrocyte invasion by merozoite. Parasite cultures with a desired synchronization window can be prepared using this method.